Impact of chitosan oligosaccharide on microbiota-metabolite-immune axis in natural aging - Liu, Wei; Shi, Pengcheng; Xiao, Yunyu; Yang, Xi; Tian, Baoming (Frontiers in Nutrition, 2026)
Natural aging involves an imbalance in gut bacteria, changes in metabolism, and mild ongoing inflammation. The integrated impact of chitosan oligosaccharide (COS) on microbiota-metabolite-immune interactions in a physiological (non-accelerated) aging context remains unclear. In this study, male C57BL/6J mice (young control; aged vehicle; aged +COS from 10 to 18 months) underwent longitudinal assessment including 16S rRNA profiling, untargeted serum metabolomics, multiplex cytokine measurement, and colonic p53 and p21 immunohistochemistry. The results showed that COS was associated with restructuring of gut community composition, with reduced Firmicutes (67.07% to 32.93%) and increased Bacteroidota (15.29% to 31.22%), alongside marked enrichment of Muribaculaceae (to 52.83%). Discriminant metabolites (VIP > 1 and FDR-adjusted) mapped predominantly to propionate (propanoate) and amino acid-linked pathways. Integrative correlation analysis connected Muribaculaceae with propionate-associated and aromatic amino acid-related metabolites and selected cytokines (including CCL20). COS mitigated age-associated body weight gain and was accompanied by reduced p53 and p21 immunoreactivity in brain and kidney, consistent with attenuation of stress associated senescence signaling. Long-term COS supplementation in naturally aged mice is associated with coordinated shifts in a putative Muribaculaceae-propionate-immune axis and concurrent down-regulation of both p53 and p21. These associative findings warrant mechanistic validation through targeted short-chain fatty acid quantification, receptor signaling assays, microbiota transfer, and functional aging endpoints to clarify causality and translational potential.